Renovation strategies of typical Danish single-family house for optimization of energy efficiency and flexibility. (November 2019) - Marszal-Pomianowska, Anna; Johra, Hicham; Loukou, Evangelia; Liu, Mingzhe; Pomianowski, Michal; Sharif, Nadin Hisham; Monne, Laia-Tuixent Morgo; Polonowa, Una
Abstract: Buildings will play a significant role in providing a safe and efficient operation of the future energy system. The aim of this work is to investigate how typical cost-effective renovation packages contribute to energy consumption reduction as well as influence the energy flexibility in a Danish single-family from 1970s, and if simple rule-based controller can contribute in peak shaving strategy. By choosing the different renovation packages, the space heating demand can decrease between 34 - 64% and the flexibility time can increase between 200 – 500%. Depending on the cut-off period, the simple RBC of turning off the heating power can further reduce the heating consumption and contribute in reducing the morning load peak with small compromise on the thermal comfort level.